Analisis Deskriptif Persepsi Pelaku UMKM Terhadap Pembiayaan Mikro Syariah - Purwanto Widodo; Faizi Faizi; Airlangga Surya Kusuma; Salma Asla Salsabila Praza; Hafizh Fadhilah Atmadja (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Due to their significant role in economic growth, Micro, Small and Medium Enterprises (MSMEs) are currently the center of attention of the government and the general public. MSMEs serve as a means to create jobs, drive economic progress, and create a private sector, so the development of MSMEs plays an important role in economic development. However, in reality, MSMEs still face many internal and external challenges, one of which is a lack of capital. Therefore, Islamic microfinance is present to assist MSME capital. The main objective of this study is to determine the extent to which MSME actors' perceptions of Islamic microfinance facilities provided by Islamic Financial Institutions (LKS). From the results of the descriptive analysis of this study, it can be seen that the majority of respondents (62%) already know or have heard about Islamic financial products. Even so, this knowledge does not move the majority of respondents to utilize Islamic financial products, where only 34% of respondents have or have had an Islamic bank account, and only 34% of respondents have or are applying for Islamic microfinance. Of the 34% or 61 respondents who have or are applying for Islamic microfinance, the nominal amount applied for by the majority is not too large, which is below 10 million rupiah. Keywords: MSMEs, Sharia Microfinance